(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The current study is set to determine the volumes of sand ripple deposits in the lower basin of Wadi Tilal in micro depositional environments by mechanical analysis. To do so, the present study analyzed samples of sediment in the laboratory using an electric sieve and the dry sieving method. The results were then calculated in the Phi unit to be processed using the Fraction V.3 program combined with the Folk & Ward equations in order to find out an estimation of the volume coefficients, and categories of statistical coefficients for the volumes of sediment sand. The study’s main findings was that the medium-sized sand category (1-2ø) constitutes about 44.75% of the weight of the ripple sand samples, and that the average sand size is about (1.698ø) and it falls within the medium-sized sand category. Moreover, the average value of the sorting coefficient was (0.873ø), which falls within the medium sorting category. In addition, most of the distribution curves fell within the high positive skewness category with an average of (0.336ø), and the value of the flattening coefficient was (1.265ø). The shape of the distribution curve falls within the category of flattened and sharpen end.